Nanocristais de Y2O3 dopados com érbio para aplicações luminescentes - Silva, Antonio Carlos Brandão (2017)
In this work, the frequency upconversion phenomenon of yttrium oxide (Y2O3) nanocrystals doped with Er3+ 2%, at three different sizes (17, 28 e 36 nm) was studied. Spectroscopic studies were performed by exciting the samples with a CW diode laser, emitting at 800 nm wavelength and measuring their emission spectra. It was also analyzed the behaviour of the luminescent emission as a function of the excitation laser power and the influence of the size of the nanocrystals on the observed luminescent emission. The performance of these nanophosphors as nanometric temperature sensors was also investigated. For this, the behaviour of the light emission spectrum of this system was analyzed, subjecting the nanoparticles to different temperatures. In these systems, the basic principle of operation is the change of the fluorescence intensity ratio (FIR) from the following levels' pairs 2H11/2 and 4S3/2, 2H11/2 and 4F9/2, and 4S3/2 and 4F9/2 of erbium ions with the sample temperature. From the obtained curves, it was possible to obtain the characteristic parameters of the sensors and their respective sensitivities. We found that the sensitivity of the temperature sensor using such crystals is rather high and this magnitude depends strongly on the crystallite size. For nanotermometers based on FIR thermally coupled between the levels (2H11/2 and 4S3/2), the sensitivity is higher for larger size nanocrystals. On the other hand, when it is used the FIR between the emitting levels thermally uncoupled (2H11/2 and 4F9/2), the highest sensitivity is obtained for the smaller nanocrystals. It was also proposed a new methodology for temperature measurement exploring, simultaneously, multiple spectral lines associated with Stark sublevels of erbium ions. This new method made it possible to obtain temperature sensors with high sensitivity over a wide temperature range. The results indicate that nanocrystals of yttria-doped erbium are very promising for thermal sensing nanoscale.